Case report: Persistence of residual antigen and RNA of the SARS-CoV-2 virus in tissues of two patients with long COVID - Goh, Denise; Lim, Jeffrey Chun Tatt; Fernaíndez, Sonia Bilbao; Joseph, Craig Ryan; Edwards, Sara Gil; Neo, Zhen Wei; Lee, Justina Nadia; Caballero, Sílvia Guerrero; Lau, Mai Chan; Yeong, Joe Poh Sheng (Frontiers in Immunology, 2022)
The World Health Organization has defined long COVID-19 (LC) as a condition where patients exhibit persistent symptoms over time after its acute phase, which cannot be explained by alternative diagnosis. Since we have previously reported residual viral antigens in tissues of convalescent patients, we now aim to assess the presence of such antigens in long COVID tissues. Here, we established the presence of residual virus within the appendix, skin, and breast tissue of 2 patients who exhibited LC symptoms, 163 to 426 days upon symptom onset. With multiplex immunohistochemistry, we detected viral nucleocapsid protein in all three tissues. The nucleocapsid protein was further observed to colocalize with macrophage marker CD68, in support of immune cells being direct targets. Additionally, with RNAscope, viral RNA was also detected. Our positive finding in the breast tissue also corroborated with recent reports that immunocompromised patients had also experienced LC symptoms and persistent viral replication. Overall, our findings, along with emerging LC studies, raises the possibility of the gastrointestinal tract functioning as a reservoir.